Inovasi Masyarakat Desa Kalikejambon dalam Pembuatan Hand Sinitizer dengan Menerapkan Teknologi Tepat Guna - Fatikhatun Nikmatus Sholihah; Ospa Pea Yuanita Meishanti; Mucharommah Sartika Ami; Anggun Wulandari (Jumat Ekonomi: Jurnal Pengabdian Masyarakat, 2022)
The people of Kalikejambon Village, Tembelang District, Jombang have several kinds of potential in the fields of agriculture, animal husbandry and natural resources. Therefore, during the Covid-19 pandemic, people must always maintain their health and hand hygiene. One of the things to maintain cleanliness is by using hand sanitizer. During the pandemic, the need for hand sanitizers continues to increase so that solutions are needed, one of which is by making hand sanistizers using natural ingredients. The ingredients used are betel leaves and lime. One of the uses of these materials is a bacterial killer substance. Both ingredients contain essential oils and anti-bacterial substances. The purpose of this service is to invite the community to innovate in using appropriate technology (TTG). The discussion and lecture method is carried out in this activity with intensive assistance. The results of the questionnaire for making hand sanistizers are that 70% of this activity can improve the community's economy, 10% of residents consider hand sanitizers as natural disinfectants and as community innovations, 8% practice skills, and 2% as experiences. However, in reality on the ground, it turns out that residents still need to learn and continue to practice their skills in making betel leaf extract and lime hand sinitizers. After this service activity, it is hoped that the community can practice skills in making the hand sinitizer. The public knows the importance of making hand sinitizer and can be made using natural materials so that people do not need expensive costs in using hand sinitizers.